Synthesis and glycosidase inhibitory studies of pentahydroxyindolizidines: D-Glucose-Derived aziridine-2-carboxylate approach - Kumar, K. S. Ajish; Chaudhari, Vinod D.; Puranik, Vedavati G.; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2007)
D-Glucose -derived aziridine-2-carboxylate I was converted into a-amino aldehyde 7, which, after Wittig olefination, asymmetric dihydroxylation, hydrogenation followed by LiAlH4 reduction, and N-Cbz protection, afforded two diastereomeric pyrrolidines 11a and 11b with sugar appendages. Removal of the 1,2-acetonide functionality in 11a/11b and reductive animation gave the pentahydroxyindolizidine alkaloids 6g and 6h, respectively, with (S) absolute configurations at the ring junctions. The glycosidase inhibitory activities of these compounds were studied.
Keywords: asymmetric dihydroxylation (AD); Iminosugars; indolizidine; N-methylmorpholine; N-oxide (NNIO)

Synthesis of 1-deoxy-1-hydroxymethyl- and 1-deoxy-1-epi-hydroxymethyl castanospermine as new potential immunomodulating agents - Vyavahare, Vinod P.; Chakraborty, Chaitali; Maity, Biswanath; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Medicinal Chemsitry, 2007)
Two new C-1 epimeric hydroxymethyl castanospermine congeners 2a and 2b, synthesized by stereocon trolled intramolecular double reductive amination Of D-glucose derived beta-keto ester as a key step, showed impressive immuno-potentiating property. The bioactivity was mediated through up-regulation of T-H1/T-H2 cytokine ratio. The finding suggested that immunmodulatory activity of polyhydroxylated indolizidine alkaloids can be tuned by minor structural/stereochemical alterations.

Synthesis of five and six membered aminocyclitols: stereoselective michael and henry reaction approach with D-glucose derived alpha,beta-unsaturated ester - Chakraborty, Chaitali; Vyavahare, Vinod P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2008)
The stereoselective intermolecular Michael addition of nitromethane to D-glucose derived alpha,beta-unSaturated ester 7 afforded L-ido-configurated nitroester 8 as the only product that on reduction of the ester functionality, cleavage of 1,2-acetonide and the intramolecular Henry reaction afforded exclusively muco-nitroinositol 9. While reduction of the ester functionality in 8, deprotection of 1,2-acetonide, oxidative cleavage with NaIO(4) and the intrarnolecular Henry reaction afforded nitrocyclopentitol 13. Nitrocyclitols 9 and 13 were converted to the hydroxyethyl substituted aminocyclohexitol 5 and aminocyclopentitol 6, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aminocyclitols; carbohydrates; Henry reaction; Michael addition; nitroinositol

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars

Synthesis of C1- and C8a-epimers of (+)-castanospermine from D-glucose derived gamma,delta-epoxyazide: intramolecular 5-endo epoxide opening approach - Kalamkar, Navnath B.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2011)
A concise synthesis of two diastereomers of (+)-castanospermine namely 1- and 8a-epi-castanospermine 1b and 1c, respectively, is reported from D-glucose. The methodology involves stereoselective cross metathesis of D-glucose derived alkene 2 with 4-bromo-1-butene followed by azide displacement and m-CPBA oxidation to afford diastereomeric gamma,delta-epoxyazides 5a/5b. The Staudinger reaction of epoxyazide 5a followed by reaction with benzylchloroformate (CbzCl) unexpectedly furnished 1,3-oxazinan-2-one derivative 7 whose stereochemistry was establish by single crystal X-ray. This helps to assign the stereochemistry in the epoxidation reaction. The reduction of 5a/5b was then carried out by transfer hydrogenation to provide gamma,delta-epoxyamine that concomitantly undergoes intramolecular 5-endo-tet cyclization to afford hydroxypyrrolidine ring skeleton with sugar framework-a precursor to castanospermine analogues 1b/1c. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Cross metathesis; D-Glucose; Epoxide; Oxazinanone; Polyhydroxy indolizidines

Sugar furanoid trans-vicinal diacid as a gamma-turn inducer: synthesis and conformational study - Vangala, Madhuri; Dhokale, Snehal A.; Gawade, Rupesh L.; Pattuparambil, Rajamohanan R.; Puranik, Vedavati G.; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2013)
A simple method for the synthesis of a sugar furanoid trans vicinal diacid and its incorporation into the N-terminal tetrapeptide sequence (H-Phe-Trp-Lys-Thr-OH) to get glycopeptide 8 has been described. 2D NMR and MD simulation studies of 8 clearly show that the sugar diacid adopts a gamma-turn conformation towards the N-terminus.

Self-assembly of fluorinated sugar amino acid derived alpha,gamma-cyclic peptides into transmembrane anion transport - Burade, Sachin S.; Saha, Tanmoy; Bhuma, Naresh; Kumbhar, Navanath; Kotmale, Amol; Rajamohanan, Pattuparambil R.; Gonnade, Rajesh G.; Talukdar, Pinaki; Dhavale, Dilip D. (Organic Letters, 2017)
Syntheses of fluorinated sugar amino acid derived alpha,gamma-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C-2 and C-3 symmetric flat oval- and triangular-ring shaped, beta-strand conformations, respectively, which appear to self assemble into nanotubes. The alpha,gamma-cyclic hexapeptide (EC50 = 2.14 mu M) is found to be a more efficient ion transporter than alpha,gamma-cyclic tetrapeptide (EC50 = 14.75 mu M). The anion selectivity and recognition of alpha,gamma-cyclic hexapeptide with NO3- ion is investigated.